Do Traditional Accounting and Economic Value Added Mediate The Relationship Between Corporate Governance and Firm Value of Indonesian State-Owned Enterprises ? - Taufik, Taufik; Wahyudi, Tertiarto; Raneo, Agung Putra; Muizzuddin, Muizzuddin; Adam, Mohamad (International Journal of Economics and Financial Issues, 2018)
The purpose of this research was to know whether traditional accounting i.e. return on asset and economic value added mediated the relationship between corporate governance and firm value of Indonesian state-owned enterprises at Indonesian stock exchange from 2012 - 2016. The population of this research was 19 of Indonesian state-owned enterprises during 2012-2016. Based on the census of sampling method applied, 19 firms were selected as sample. Path Analysis was conducted to shows its direct and indirect effects of each path. The result showed that both traditional accounting i.e. return on asset and economic value added did not mediate the relationship between corporate governance and firm value of Indonesian state-owned enterprises at Indonesian stock exchange during 2012-2016. In other words, corporate governance did not effect indirectly on firm value through both traditional accounting i.e. return on asset and economic value added. Another interesting finding was that although economic value added was not as a mediation but it influenced firm value while traditional accounting i.e. return on asset had no effect on firm value. This research only focused on Indonesian state-owned enterprises. For further research, it is recommended to include all firms listing at Indonesian stock exchange. The findings have implication for management of Indonesian state-owned enterprises to strengthen corporate governance with respect to transparency accountability, responsibility, independency and fairness to be an influential factors of traditional accounting i.e. return on asset and economic value added. The result of this research is important for investors by highlighting the significant relationship between corporate governance on firm value and insignificant relationship between corporate governance to traditional accounting i.e. return on asset and economic value added. To best of our knowledge this research is a preliminary attempt contributing to the literature by the use of economic value added as a mediation for the relationship between corporate governance on firm value. Keywords: Corporate governance, Traditional accounting, Economic value added, Indonesian state-owned enterprises, Indonesian Stock Exchange. JEL Classifications: G32, M41, O16